Classical Analog of Extended Phase Space SUSY and Its Breaking. (30th May 2013) - Ter-Kazarian, Gagik
Abstract : We derive the classical analog of the extended phase space quantum mechanics of the particle with odd degrees of freedom which gives rise to (N = 2 )-realization of supersymmetry (SUSY) algebra. By means of an iterative procedure, we find the approximate ground state solutions to the extended Schrödinger-like equation and use these solutions further to calculate the parameters which measure the breaking of extended SUSY such as the ground state energy. Consequently, we calculate a more practical measure for the SUSY breaking which is the expectation value of an auxiliary field. We analyze nonperturbative mechanism for extended phase space SUSY breaking in the instanton picture and show that this has resulted from tunneling between the classical vacua of the theory. Particular attention is given to the algebraic properties of shape invariance and spectrum generating algebra.